Alzheimer's Disease May Benefit from Olive Oil Polyphenols: A Systematic Review on Preclinical Evidence Supporting the Effect of Oleocanthal on Amyloid-β Load - Zupo, Roberta; Castellana, Fabio; Panza, Francesco; Solfrizzi, Vincenzo; Lozupone, Madia; Tardugno, Roberta; Cicero, Nicola; Corbo, Filomena; Crupi, Pasquale; Sardone, Rodolfo; Clodoveo, Maria Lisa (Current Neuropharmacology, 2025)
BackgroundMediterranean diet may enhance cognitive function and delay the progression of Alzheimer's disease (AD). We conducted a systematic review to investigate the effect of oleocanthal (OC) from extra-virgin olive oil (EVOO) on amyloid-β (Aβ) burden in preclinical models of AD, considering the anti-inflammatory and neuroprotective effects of EVOO biophenols, which are key components of the Mediterranean dietary model.MethodsThe literature was searched through six electronic databases until February 2023. Screening of 52 retrieved articles for inclusion criteria resulted in 7 preclinical reports evaluating the effect of an OC-supplemented diet on AD trajectories by means of Aβ load or clearance in affected models. Reports were appraised for risk of bias using the SYRCLE's RoB tool. A protocol was registered on PROSPERO.ResultsCase control prevailed over the case-crossover design, and the geographical distribution was uniformly American. The study population mostly included 5xFAD, otherwise TgSwDI or wild-type C57BL/6 mouse models. We found a role of OC in reducing Aβ load in the hippocampal parenchyma and microvessels compared with controls. An increased cerebral clearance of Aβ through the blood-brain barrier and a substantial improvement in metabolic and behavioral parameters were also reported in preclinical models under an OC-enriched diet. The risk of bias was shown to be moderate overall.ConclusionPreclinical data are promising about the effects of OC from the Mediterranean diet's EVOO in relieving the burden of Aβ in AD; however, further evidence is needed to corroborate the efficacy of this biophenol and strengthen the speculated causal pathway.
Keywords: amyloid-β